The value of adding graded levels of gelatinized sorghum grain to a fattening ration - Drake, C.L.; Brent, B.E.; Deyoe, C.W.; Post, H.B. (Kansas Agricultural Experiment Station, 2011)
Reports from several experiment stations have aroused much interest in the value of “steam processing” or “flaking” grain for beef cattle. During the process, some gelatinization or cooking of the grain occurs. This trial studied the addition of various amounts of completely gelatinized sorghum grain to fattening steers rations.
Keywords: Beef; Sorghum grain; Steam flaking; Flaking